Symbolism in Hemingway’s The Short Happy Life of Francis Macomber - Adaninggar Septi Subekti; Aprilia Kristiana Tri Wahyuni (Universitas Lambung Mangkurat, 2021)
This paper analysed Ernest Hemingway’s The Short Happy Life of Francis Macomber using New Criticism framework on symbolism. Comparisons of drinks, clothes, and colours paralleled the difference between Francis, a wealthy yet unconfident man, and Wilson, a man of masculinity. The next was the sitting positions of the characters in the car in which front seat symbolised authority and power whereas back seat inferiority and lack of confidence. Car symbolised protection, segregation, and power for Margot, whereas camp, and savannah foresaw Francis’ transformation from a wealthy person of comfort (camp) to a man of manly conviction signified with savannah offering wilderness. This transformation was also attributed to Francis’ overcoming obstacles symbolised with a lion and buffalos. Guns and rifles possessed by male characters indicated their dominance with Margot, the only female, practically left-out, except by the end of the story when she wielded a rifle shooting Francis dead.